Impact of cell wall non-cellulosic and cellulosic polymers on the mechanical properties of flax fibre bundles. (1st September 2022) - Gautreau, Maxime; Durand, Sylvie; Paturel, Angeline; Le Gall, Sophie; Foucat, Loic; Falourd, Xavier; Novales, Bruno; Ralet, Marie-Christine; Chevallier, Sylvie; Kervoelen, Antoine; Bourmaud, Alain; Guillon, Fabienne; et al.
Abstract: Fibre bundles are groups of elementary fibres glued together thanks to the middle lamella, and are the main fraction in plant fibre composites. In this study, relationship between the mechanical properties of flax fibre bundles, chemical composition and cellulose structure were investigated. To do so, a sequential biopolymer extraction was implemented. Fibre bundles were first depectinated by oxalate extraction, and then the hemicelluloses were extracted by LiCl/dimethyl sulfoxide (DMSO) and KOH. The oxalate extract consisted of homogalacturonans and type I rhamnogalacturonans, while the LiCl extract was composed mainly of glucomannans and the KOH extract of xyloglucans. The KOH stage resulted in the appearance of cellulose II in flax bundles. The extraction of pectin and hemicelluloses led to the disappearance of the middle lamella concomitant with a decrease in the tensile Young's modulus and maximum strength. Finally, the fibre bundle composition, ultrastructure and mechanical properties are discussed together in view of the thin middle lamella. Graphical abstract: Unlabelled Image